A Study of the Macrostructure of Written Proposals by Professionals from the Malaysian Business Community - Nair, Anne Benedict (Journal of Modern Languages, 2017)
This study seeks to explore the discoursal development of a particular genre by examining the macrostructure of exemplars produced by active members of the discourse community. Doing studies such as the present study is an effective way of examining discoursal development as the macrostructure essentially reflects the communicative message of a text.